Pengaruh Label Sertifikasi Halal terhadap Aktivitas Pelaku Usaha Kuliner dan Wisatawan Non-Muslim di Palembang - Enos Julvirta; Mustika Permatasari; Umi Dian Adhitya Wulan Ningrum; Raty Rusmiana; Rikki Nelson Lumban Gaol (SIGn Jurnal Hukum, 2021)
This study aims to determine the effect of halal certification labels on the sale of culinary products in Palembang. Furthermore, this study also wants to know the competitiveness of business actors who have halal certification in Palembang. In addition, to determine the perception of non-Muslim tourists on halal product certification in Palembang. This type of study is empirical research. The questionnaire method was used to obtain research data. The data obtained in this study refer to the problem hypothesis testing. Bivariate linear regression was used as a test tool on the halal label variable to predict an increase in sales and competitiveness and was calculated by SPSS 22. At the same time, explanatory sequential design as a qualitative analysis method is obtained from the description of the questionnaire data. It is used to explain non-Muslim perceptions of halal products. The results of this study indicate several conclusions. First, the sale of culinary products has increased positively with the existence of halal certification labels. In this case, halal certification labels affect the sale of culinary products in Palembang is 19.1%. Second, the competitiveness of business actors has increased positively with halal certification labels. In this case, halal certification labels affect the competitiveness of business actors in Palembang is 8.2%. Third, most non-Muslim tourists have a good perception of the halalness of culinary products in Palembang. In this case, 94.31% of respondents have a good perception of the halalness of a culinary product. Meanwhile, 5.69% of respondents have a bad perception. Therefore, it is recommended for socialization related to the role of halal certificate labels to the general public and culinary business actors in Palembang. In addition, a collaboration between the Association, Community, Government, and Media is needed to encourage culinary business actors in Palembang to play an active role in having a halal certificate label. Next, invite BPJPH to provide information about the steps for registering a halal certificate label.